2006
DOI: 10.1016/j.najef.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Financial development and financial liberalization in Asia: Thresholds, institutions and the sequence of liberalization

Abstract: I investigate whether financial openness leads to financial development after controlling for the level of legal/institutional development, and whether trade opening is a precondition for financial opening, focusing on Asia. Utilizing a panel encompassing 87 less developed countries over the period 1980 to 2000, I find that a higher level of financial openness spurs equity market development only if a threshold level of legal development has been attained, a condition prevalent particularly among emerging mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 57 publications
3
44
0
4
Order By: Relevance
“…China has focused more on liberalization of product markets since the late 1970s. Its financial liberalization has generally been cautious, lagging behind many Asian developing nations (Ito, 2006). Does this asymmetric liberalization approach, especially its emphasis on financial restraints or gradual financial liberalization, provide a more appropriate model for developing countries embarking on economic reforms?…”
Section: Introductionmentioning
confidence: 99%
“…China has focused more on liberalization of product markets since the late 1970s. Its financial liberalization has generally been cautious, lagging behind many Asian developing nations (Ito, 2006). Does this asymmetric liberalization approach, especially its emphasis on financial restraints or gradual financial liberalization, provide a more appropriate model for developing countries embarking on economic reforms?…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the experiences are used to broaden the knowledge and understanding of the process and have resulted in great learnings from past mistakes. Amongst others, Ito (2006) has studied the process of financial Global Finance Journal 19 (2009) equity market index returns show that there is a very weak, positive, relatively constant conditional correlation with the Asia-Pacific region, and also weak but very volatile and mainly negative conditional correlation with the rest of the world. Based on the results and findings in this paper it can be concluded that the process of integration of the BRIC countries with their respective regions and globally is relatively low at this stage, however it is expected to continue to progress further given the initiatives undertaken by the countries' policy makers stimulating the level of cross-country openness.…”
Section: Introductionmentioning
confidence: 99%
“…There are few case studies or methodologies applied to special groups of countries, Naceur et al (2008) analyzed a sample of 11 countries of the Middle East and North Africa region, Ito (2006) put special attention on 15 Asian countries, Ahn (2008) analyzed Korea, and Law (2008) studied Malaysia.…”
Section: Analysis Of the Previous Empirical Evidencementioning
confidence: 99%